A family of simulation criteria to guide DEVS models validation rigorously, systematically and semi-automatically - Hollmann, Diego Ariel (2014)
The most common method to validate a DEVS model against the requirements is to simulate it several times under different conditions, with some simulation tool. The behavior of the model is compared with what the system is supposed to do. The number of different scenarios to simulate is usually infinite, therefore, selecting them becomes a crucial task. This selection, actually, is made following the experience or intuition of an engineer. Here we present a family of criteria to conduct DEVS model simulations in a disciplined way and covering the most significant simulations to increase the confidence on the model. This is achieved by analyzing the mathematical representation of the DEVS model and, thus, part of the validation process can be automatized.